Pengaruh Kualitas Pelayanan dan Kelengkapan Produk terhadap Keputusan Pembelian di Apotek Winola Medika Maumere - Nelfiana Nggagho; Antonius Philipus Kurniawan; Yosef Tonce (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The background of this research is how much effect service quality and product completeness have on purchasing decisions at Winola Medika Maumere Pharmacy. This research aimed to (1) determine the description of service quality and product completeness on purchasing decisions at Winola Medika Maumere Pharmacy, (2) Know the effect of service quality on purchasing decisions at the Winola Medika Maumere Pharmacy, (3) Know the effect of product completeness on purchasing decisions at the Winola Medika Maumere Pharmacy, (4) Know the simultaneous effect of service quality and product completeness on purchasing decisions at the Winola Medika Maumere Pharmacy. The population in this research were consumers who bought products at the Winola Medika Maumere Pharmacy using the Lemeshow formula. The sample in this research amounted to 100 respondents. Data was collected through questionnaires and analyzed through descriptive statistical methods and multiple linear regression statistics. Hypothesis testing was done through a partial tests